The Tenants of Emperor Haile Selassie I: An Examination of Landlord-Tenant Relationship - Bogale, Wagaw (Ethiopian Journal of Social Sciences, 2018)
Different scholars have examined Ethiopian tenancy from various angles. Previous studies on the subject consistently observe that the bulk of the southern peasants became tenants following the expansion of Ethiopian Empire State in the late nineteenth century and tenancy in the South was more common and more onerous than it was in the north. In addition, there was little reason to believe that the Imperial Ethiopian Government provided practical legal provisions to improve the conditions of tenants in Ethiopia. Nevertheless, the position of most scholars regarding the condition of tenants as very gloomy is very difficult to accept.  A closer examination of the relationship that existed between the Bétä Rist, the management institution for the private property of Emperor Haile Selassie I, and the monarch’s tenants appears to suggest otherwise. Examining the historical processes that gave rise to the reduction of many peasants to the status of tenants; its intensity when analysed from two crudely delimited geographical regions (north and south), and the prerequisites that were necessary to undertake any land reform policy in the country are, however, beyond the scope of this paper. This study focuses on how the Bétä Rist regulated landlord-tenant relationships in the postItalian  period. It examined the personal, refers to Emperor Haile Selassie I, and institutional concerns taken to protect their rights as a tenant, and improve their conditions in light of government initiatives made to improve the conditions of tenants by taking into account the following basic organizing concepts: types of tenants, forms of rentals, security of tenure, and tenancy agreements. The researcher approached the issue qualitatively. The study used archival materials culled from Welde Mesqel Tariku Memorial Research Centre of the Institute of Ethiopian Studies and from secondary literature.